Effective catalytic hydrodechlorination removal of chloroanisole odorants in water using palladium catalyst confined in zeolite Y. (December 2022) - Zhang, Yufan; Ma, Pu; Fu, Heyun; Qu, Xiaolei; Zheng, Shourong
Abstract: Chloroanisoles is a class of odorous pollutants commonly identified in drinking water. In the present study, we confined noble metal palladium (Pd) in the micropores of zeolite Y ( ie -Pd@Y) using an ion exchange method, and applied it for the catalytic hydrodechlorination removal of chloroanisoles (represented by 2, 4, 6-trichloroanisole/TCA) in water. Pd supported on zeolite Y surface ( im -Pd/Y, prepared by conventional impregnation method) was used as the benchmarking catalyst. The characterization results revealed that ie -Pd@Y had smaller Pd particle size and higher Pd n+ /Pd 0 ratio than im -Pd/Y. The catalytic hydrodechlorination of TCA followed a concerted dechlorination pathway and the Langmuir-Hinshelwood model. The ie -Pd@Y catalysts with different Pd loadings exhibit excellent catalytic activities with more than 95% of TCA removed within 30 min, which is far superior to the im -Pd/Y catalysts (27–70%). Moreover, due to the confinement effect of zeolite Y, ie -Pd@Y displayed enhanced catalytic stability as compared with im -Pd/Y. The initial activity of ie -Pd@Y was more than 20 times higher than that of im -Pd/Y after five reaction cycles. Additionally, with the assistance of sieving effect, ie -Pd@Y displayed much stronger capability against the interference from dissolved organic matter than im -Pd/Y. The present results demonstrate that the confined catalysts ie -Pd@Y can be applied in liquid phase catalytic hydrogenation to effectively eliminate halogenated odorants in waters. Graphical abstract: Image 1 Highlights: Pd catalyst confined in zeolite Y was used for the removal of chloroanisole odorants. The confinement effect of zeolite pore rendered Pd enhanced activity and stability. The catalyst had strong DOM resistance due to the sieving effect of zeolite micropore.